2012
DOI: 10.1371/journal.pone.0034284
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Synthetic-Fibrin Scaffold Supports Growth and Cardiomyogenic Commitment of Human Placental Derived Stem Cells

Abstract: AimsA potential therapy for myocardial infarction is to deliver isolated stem cells to the infarcted site. A key issue with this therapy is to have at one's disposal a suitable cell delivery system which, besides being able to support cell proliferation and differentiation, may also provide handling and elastic properties which do not affect cardiac contractile function. In this study an elastic scaffold, obtained combining a poly(ether)urethane-polydimethylsiloxane (PEtU-PDMS) semi-interpenetrating polymeric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 72 publications
0
45
0
Order By: Relevance
“…In addition, scaffolds loaded with releasable growth factors, again targeting regeneration, are under continuous development. In this context, polyurethane-fibrin complexes [43], electrospun fibers loaded with growth factor-encoding expressible DNA [44], TGF-b-loaded fibrin scaffolds [45], PDGF-loaded electrospun PLGA/PEG-PLA composite [46] and FGF-1-loaded PEGDA hydrogels [47] are a few recent examples among the wide spectrum illustrating these approaches.…”
Section: Future Science Groupmentioning
confidence: 99%
“…In addition, scaffolds loaded with releasable growth factors, again targeting regeneration, are under continuous development. In this context, polyurethane-fibrin complexes [43], electrospun fibers loaded with growth factor-encoding expressible DNA [44], TGF-b-loaded fibrin scaffolds [45], PDGF-loaded electrospun PLGA/PEG-PLA composite [46] and FGF-1-loaded PEGDA hydrogels [47] are a few recent examples among the wide spectrum illustrating these approaches.…”
Section: Future Science Groupmentioning
confidence: 99%
“…Placenta-derived mesenchymal stromal cells (PMSCs) are analogous to the MSCs routinely obtained from bone marrow in both surface marker expression and multipotency [20,21] . Investigators interested in utilizing PMSCs or other fetal-derived mesenchymal stromal cells have demonstrated their potential for engineering bone [22][23][24] , cartilage [25][26][27] , and muscle [28][29][30] , as well as pancreatic [31] , neural [7,17] and cardiac tissues [18,[32][33][34] . The gestational age of the source tissue may affect the therapeutic capabilities of the cells.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, biosimulation of cardiac microenvironment into the scaffolds is an important matter to determine the output of heart tissue engineering. Specifically, all of the cardiac microenvironment components including growth factors [Lin et al, ; Lisi et al, ], decellularized tissue matrices [Xu et al, ] and synthetic polymer scaffolds [Parrag et al, ; Crowder et al, ] are as key matters to achieve the effective injured heart masculinization and revascularization. Moreover, preserving the survival and function of the seeded cell against the low oxygen and nutrient condition [Kawamura et al, ] is a crucial feature for heart tissue engineering efficiency which it has a close relationship with biosimulation of the cardiac microenvironment.…”
Section: Cell Therapymentioning
confidence: 99%
“…It has been shown that interaction of cells with scaffold components through promoting the various signaling pathways can control the cells survival as well as stem cells proliferation, differentiation, and also formation of functional tissue [Kaiser and Coulombe, ]. Currently, the combination of several growth factors with scaffolds such as VEGF, b‐FGF, PDGFBB [Lin et al, ; Lisi et al, ; Matsuda et al, ] and IGF‐1 [Karam et al, ] is known to be an appropriate method for regulating the engineered tissue microenvironment and also for controlling the survival of the cells, and their differentiation. Different cardiac ECM proteins like Gsn, Vdac2, and Hspa1l are reported as the significant cellular regulators which inhibit the cell death and control the actin filaments assembly and disassembly [Sun et al, ; Baraniak and McDevitt, ].…”
Section: Cell Therapymentioning
confidence: 99%